1995
DOI: 10.1210/mend.9.5.7565808
|View full text |Cite
|
Sign up to set email alerts
|

Gonadal tumorigenesis in transgenic mice bearing the mouse inhibin alpha-subunit promoter/simian virus T-antigen fusion gene: characterization of ovarian tumors and establishment of gonadotropin-responsive granulosa cell lines.

Abstract: To establish in vivo gonadal tumor models and permanent lines of gonadal somatic cells we produced transgenic (TG) mice expressing the Simian virus (SV) 40 T-antigens (T-ag), driven by 6 or 2.1 kilobase fragments of the mouse inhibin alpha-subunit promoter. Hitherto, altogether 44 TG mice, one of which carried the shorter transgene, have produced gonadal tumors. Two founder females expressing the longer transgene, KK1 and KK3, and three established TG mouse lines were studied in detail. Penetrance of the pheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(22 citation statements)
references
References 0 publications
1
21
0
Order By: Relevance
“…As shown previously (Kananen et al, 1995(Kananen et al, , 1996a, these mice develop gonadal tumors originating from Leydig and granulosa cells, with 100% penetrance, at the age of 5-6 months. To find out whether the extragonadal tumors frequently found in these mice were primary or because of metastases of gonadal tumors, we gonadectomized neonatal mice (Kananen et al, 1996b).…”
Section: Introductionsupporting
confidence: 73%
See 2 more Smart Citations
“…As shown previously (Kananen et al, 1995(Kananen et al, , 1996a, these mice develop gonadal tumors originating from Leydig and granulosa cells, with 100% penetrance, at the age of 5-6 months. To find out whether the extragonadal tumors frequently found in these mice were primary or because of metastases of gonadal tumors, we gonadectomized neonatal mice (Kananen et al, 1996b).…”
Section: Introductionsupporting
confidence: 73%
“…The weights of the ovaries of double TG and bLHb-CTP mice showed no significant difference at 3 months, but the former were markedly larger at the age of 5 months (Figure 1a). At the age of 3 months double TG mice presented with highly proliferating tumors with mitotic figures (Figure 1b), akin to those seen in Inha/Tag mice at an older age and shown to be of granulosa cell origin (Kananen et al, 1995), and they had luteinized follicles, as found in bLHb-CTP mice (Risma et al, 1995) ( Figure 1b). The granulosa cell origin of these tumors was reconfirmed by aromatase-specific immunostaining (Figure 3b).…”
Section: Gonadal Tumorigenesis In Double Tg Blhb-ctp/inha/ Tag Micementioning
confidence: 73%
See 1 more Smart Citation
“…In contrast, only a background level of staining is seen in the stromal region of non-TG ovaries (Figure 4). The human mutant LPA 2 (Edg-4) TG mice were expected to have high levels of LPA 2 expression in the sex cordstromal compartment of their ovaries based on the known targeting properties of mouse a-inhibin large promoter (Kananen et al, 1995;Hsu et al, 1996). There are also consistently many more prominent nodules composed of luteinized cells observed in the TG ovaries than in age-matched wild-type ovaries.…”
Section: Resultsmentioning
confidence: 99%
“…Human LPA 2 (Edg-4) TG mice were generated by injecting C57BL/6 oocytes with a minigene consisting of a 1053 bp cDNA encoding human mutant LPA 2 , with a C-terminal cytoplasmic tail 35 amino acids longer than that of the wildtype LPA 2 , coupled to the XbaI site of the 6 Kb a-subunit of the mouse inhibin promoter (Kananen et al, 1995;Hsu et al, 1996). Human LPA 2 TG mice were identified by slot blot and PCR analyses of tail-tissue genomic DNA (Laird et al, 1991).…”
Section: Tg Micementioning
confidence: 99%